Heterogeneous formation of nitryl chloride and its role as a nocturnal NOx reservoir species during CalNex‐LA 2010. Issue 18 (24th September 2013) - Mielke, L. H.; Stutz, J.; Tsai, C.; Hurlock, S. C.; Roberts, J. M.; Veres, P. R.; Froyd, K. D.; Hayes, P. L.; Cubison, M. J.; Jimenez, J. L.; Washenfelder, R. A.; Young, C. J.; et al.
Abstract [1] The nocturnal conversion of dinitrogen pentoxide (N2O5) to nitryl chloride (ClNO2) on chloride‐containing aerosol can be a regionally important NOx (= NO + NO2) recycling and halogen activation pathway that affects oxidant photochemistry the following day. Here we present a comprehensive measurement data set acquired at Pasadena, California, during the CalNex‐LA campaign 2010 that included measurements of odd nitrogen and its major components (NOy = NOx + NO3 + 2N2O5 + ClNO2 + HNO3 + HONO + peroxyacyl, alkyl, and aerosol nitrates) and aerosol size distribution and composition. Nitryl chloride was present during every night of the study (median mixing ratio at sunrise 800 pptv) and was usually a more significant nocturnal NOx and odd oxygen (Ox = O3 + NO2 + 3N2O5 + ClNO2) reservoir species than N2O5 (whose concentrations were calculated from its equilibrium with NO2 and NO3). At sunrise, ClNO2 accounted for 21% of NOz (=NOy − NOx), 4% of NOy, and 2.5% of Ox, respectively (median values). Kinetic parameters for the N2O5 to ClNO2 conversion were estimated by relating ClNO2 concentrations to their time‐integrated heterogeneous production from N2O5 and were highly variable between nights. Production of ClNO2 required conversion of N2O5 on submicron aerosol with average yield (φ) and N2O5 reactive uptake probability (γ) of γφ = 0.008 (maximum 0.04), scaled with submicron aerosol chloride content, and was suppressed by aerosol organic matter and liquid water content. Not all of the observed variability of ClNO2 production efficiency could be rationalized using current literature parameterizations.